GATA‐3‐specific DNAzyme — A novel approach for stratified asthma therapy. Issue 1 (January 2017) - Garn, Holger; Renz, Harald
Abstract : Type‐2 immune mechanisms drive inflammation in about 50% of asthma patients. Given that GATA‐3 is a master regulator of Type‐2 cytokine pathways, therapies targeting this pathway are attractive. Antisense technologies such as a GATA‐3‐specific DNAzyme–which has an inherent RNA‐cleaving activity–are being tested for the treatment of type‐2‐driven asthma. Abstract : It is now well established that type‐2 immune mechanisms drive the inflammation in about 50% of asthma patients. The major cellular and molecular players regulating this important network have been identified. In terms of therapeutic intervention, cytokine and cytokine‐receptor pathways have been given major attention, since these molecules are relatively easily accessible for a blockade through monoclonal antibodies, and a number of positive clinical results support this concept. However, targeting events controlling the type‐2 immunity network upstream of selective cytokine pathways would be equally attractive. Type‐2 immunity is regulated through a delicate interplay of several transcription factors (including GATA‐3, STAT‐6, NFAT, IRF4, c‐maf), with GATA‐3 as master regulator in this regard. Since transcription factors are intracellularly located they cannot be directly targeted by monoclonal antibodies. For intracellular targets, antisense technologies such as antisense DNA and siRNA have been shown to be a promising approach, and have recently made major advances toward clinical application. Here, we summarize the development of a GATA‐3‐specific DNAzyme–a molecule class that combines the superior specificity of antisense molecules with an inherent RNA‐cleaving enzymatic activity–for the treatment of type‐2‐driven asthma from preclinical development toward a proof‐of‐concept clinical study.